(untitled) (TERRA LATINOAMERICANA, 2025)
The impact of global warming on cof fee crops has made it necessary to seek strategies that promote resilient plantations capable of withstanding increasingly frequent and intense drought periods. This study evaluated the incorporation of biochar and microorganisms in cof fee seedlings to assess the resistance of plants to diseases and water stress. The trial was conducted in randomly subdivided plots with normal and interrupted irrigation, dif ferent combinations of biochar and microorganisms, and four cof fee varieties. The response variables included plant height, fresh weight, leaf area, nutrient content, disease incidence and severity, and soil physicochemical properties. By incorporating biochar with microorganisms, plants under water stress did not increase their root development compared with the other treatments; however, dif ferences of 6 to 8 cm in height were observed, with up to three times more biomass among varieties and greater nutritional balance at the leaf level. Although the incidence of diseases did not decrease, their severity was reduced. The Obatá variety, with the combination of biochar and microorganisms, showed better growth performance under water stress conditions compared with the control, as well as lower disease severity. In addition, the application of biochar and microorganisms to the soil reduced acidity, increased cation exchange capacity, electrical conductivity, and the carbon/nitrogen ratio, improved phosphorus levels, and decreased iron content. Therefore, the application of biochar and microorganisms may be considered a potential strategy for managing cof fee seedlings to enhance their growth and resistance to water stress.